The interface between phosphatidylinositol transfer protein function and phosphoinositide signaling in higher eukaryotes - Grabon, Aby; Bankaitis, Vytas A.; McDermott, Mark I. (Journal of lipid research, 2019)
Phosphoinositides are key regulators of a large number of diverse cellular processes that include membrane trafficking, plasma membrane receptor signaling, cell proliferation, and transcription. How a small number of chemically distinct phosphoinositide signals are functionally amplified to exert specific control over such a diverse set of biological outcomes remains incompletely understood. To this end, a novel mechanism is now taking shape, and it involves phosphatidylinositol (PtdIns) transfer proteins (PITPs). The concept that PITPs exert instructive regulation of PtdIns 4-OH kinase activities and thereby channel phosphoinositide production to specific biological outcomes, identifies PITPs as central factors in the diversification of phosphoinositide signaling. There are two evolutionarily distinct families of PITPs: the Sec14-like and the StAR-related lipid transfer domain (START)-like families. Of these two families, the START-like PITPs are the least understood. Herein, we review recent insights into the biochemical, cellular, and physiological function of both PITP families with greater emphasis on the START-like PITPs, and we discuss the underlying mechanisms through which these proteins regulate phosphoinositide signaling and how these actions translate to human health and disease.